2011
DOI: 10.1016/j.ijrmms.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of abandoned and closed roadways in the Kushiro Coal Mine, Japan

Abstract: The objective of this research is to clarify the mechanical properties and self-healing ability of ExcavationDamaged Zone (EDZ)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 1 publication
(3 reference statements)
0
17
0
Order By: Relevance
“…However, the influence of the humidity on the fracture toughness of rock has yet to be fully explored. Fujii et al (2011) reported that several large rock falls occurred in humid summer in Kushiro Coal Mine in Japan due to the weakening of rock by inflow of humid air. This report suggests that the investigation of the humidity effects on fracture toughness of rock is important for ensuring the stability of structures in a rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of the humidity on the fracture toughness of rock has yet to be fully explored. Fujii et al (2011) reported that several large rock falls occurred in humid summer in Kushiro Coal Mine in Japan due to the weakening of rock by inflow of humid air. This report suggests that the investigation of the humidity effects on fracture toughness of rock is important for ensuring the stability of structures in a rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…29 As described in Section 1, in the Kushiro Coal Mine, rock falls often happen when humidity is high. 7 When a decrease in P-wave velocity in a rock mass is observed to coincide with an increase of humidity, failure from the surface of the rock mass may well be imminent. The results of this study offer fundamental information concerning the weakening of a rock mass structure.…”
Section: Discussionmentioning
confidence: 99%
“…6 Humidity is known to affect strength and fracturing in rock. For example, Fujii et al 7 reported that the strength of sandstone in Kushiro Coal Mine in Japan (Kushiro sandstone) decreases as water content rises. According to, 7 rock fall is common in a mining gallery in Kushiro Coal Mine during summer when the relative humidity is high.…”
Section: Introductionmentioning
confidence: 99%
“…The former are zones of mainly elastic disturbance whereas the latter are zones that have irrecoverable damage [Tsang et al, 2005]. Stress redistribution and permeability changes within these zones [Sato et al, 2000;Fujii et al, 2011;Tsang et al, 2005] can affect the sealability. This represents the tightness of an opening and is defined as inversely proportional to the flow velocity per unit pore pressure gradient of the surrounding rock mass, due to hydromechanical (HM) coupling.…”
Section: Introductionmentioning
confidence: 99%